Marketing and sales analytics : proven techniques and powerful applications from industry leaders - Brea, Cesar A. (Pearson, 2014)
Today, the effective marketing analytics executive is even more important than the brilliant data scientist. That's because successful analytics investments now require executive-level orchestration of many elements that go far beyond conventional definitions of analytics. Marketing and Sales Analytics examines the experiences of sales/marketing leaders and practitioners who have successfully built high value analytics capabilities in multiple industries. Then, drawing on their experiences, top analytics consultant Cesar Brea introduces overarching frameworks and specific tools that can help you achieve the same levels of success in your own organization. Brea shows how to: Establish the "ecosystemic" conditions for analytic success Reconcile the diverse perspectives that impact analytics initiatives ("Business v. IT," "Sales v. Marketing," "Analysts v. Creatives v. Managers," and "Everyone v. Finance") Decide what success will "look like" Agree on the questions to ask Organize both internal and external data Establish operational flexibility, and balance flexibility with efficiency Recruit the right people and organize them optimally Intelligently decide what to do yourself, and what to hire vendors for Balance research, analytics, and testing Implement proven research, analytics, and testing strategies Deliver results through storytelling (and recognize its limitations) Control the biases that creep into analytics research Maintain momentum, implement governance, and "keep score."